2022
DOI: 10.3390/ma15041318
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Driven Photocatalytic Inactivation of Bacteria, Bacteriophages, and Their Mixtures Using ZnO-Coated HDPE Beads as Floating Photocatalyst

Abstract: Semiconductor materials used as photocatalysts are considered among the most effective ways to treat biologically polluted water. Certainly, efficiency depends on the selection of photocatalyst and its substrate, as well as the possibility of its application in a broader spectrum of light. In this study, a reactive magnetron sputtering technique was applied for the immobilisation of ZnO photocatalyst on the surface of HDPE beads, which were selected as the buoyant substrates for enhanced photocatalytic perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The floating photocatalyst can achieve the maximum oxidation and the best light radiation, greatly improving the generation of free radicals and photocatalytic efficiency [ 52 ]. Urbonavicius et al [ 53 ] prepared ZnO-based floating photocatalysts with high-density polyethylene (HDPE) spheres with and without a Ni underlayer as the floatable substrate, respectively, and the ZnO film was deposited onto the HDPE sphere (denoted as ZnO-HDPE). It was found that the use of the ZnO-HDPE photocatalyst could inactivate the phage mixture under visible-light irradiation.…”
Section: Modified Ultraviolet-response Composite Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The floating photocatalyst can achieve the maximum oxidation and the best light radiation, greatly improving the generation of free radicals and photocatalytic efficiency [ 52 ]. Urbonavicius et al [ 53 ] prepared ZnO-based floating photocatalysts with high-density polyethylene (HDPE) spheres with and without a Ni underlayer as the floatable substrate, respectively, and the ZnO film was deposited onto the HDPE sphere (denoted as ZnO-HDPE). It was found that the use of the ZnO-HDPE photocatalyst could inactivate the phage mixture under visible-light irradiation.…”
Section: Modified Ultraviolet-response Composite Materialsmentioning
confidence: 99%
“… Infectivity of separate PRD1 and T4 phages and their mixture under visible-light irradiation for 1 h using ZnO-HDPE ( a ) without Ni underlayer and ( b ) with Ni underlayer. Reproduced from [ 53 ], Materials, with permission from MDPI Press 2022. …”
Section: Figurementioning
confidence: 99%